REVIU ANALISIS : KARAKTERISTIK DEWAN DENGAN KINERJA KEUANGAN PERUSAHAAN - Elis Elis; Agus Munandar (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2023)
The purpose of this study is to deepen understanding and describe the diversity of research results from the characteristics of the board and the company's financial performance. This research method is an analytical review by collecting studies on board characteristics and company financial performance. The results of data from 17 research articles that meet the required requirements were obtained from Google Scholar throughout 2019 to 2021. The results of the research are inconsistent from the characteristics of the board, namely: independent commissioners, board size, board meetings, board gender, board age, tenure board, and board education on organizational financial performance.